2008
DOI: 10.1021/ie8006006
|View full text |Cite
|
Sign up to set email alerts
|

Vapor−Liquid Equilibrium Study in Trickle-Bed Reactors

Abstract: Vapor-liquid equilibrium (VLE) in trickle-bed hydroprocessing reactors can significantly change the fluid hydrodynamics and the distribution of reacting species in both the vapor and liquid phases and, ultimately, change the reactor performance. VLE is especially important to pilot-plant studies in which ideal operating regimes (plug flow, full catalyst wetting, absence of reactor wall effects, etc.) are desired to generate reliable, reproducible, and representative data for commercial scale-up and kinetics st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
60
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(63 citation statements)
references
References 22 publications
3
60
0
Order By: Relevance
“…To obtain reliable and reproducible results in hydrotreating of mixtures with wide fractional composition, it is particularly important to determine the mode in which the gas-raw material mixture moves within the reactor. For practical purposes, a number of criteria are used to evaluate the reaction mode [9]. The displacement condition should be satisfi ed for the fl owthrough reactor with a stationary bed (in this case, the diffusion in the transverse cross-section of the reactor can be neglected).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To obtain reliable and reproducible results in hydrotreating of mixtures with wide fractional composition, it is particularly important to determine the mode in which the gas-raw material mixture moves within the reactor. For practical purposes, a number of criteria are used to evaluate the reaction mode [9]. The displacement condition should be satisfi ed for the fl owthrough reactor with a stationary bed (in this case, the diffusion in the transverse cross-section of the reactor can be neglected).…”
Section: Resultsmentioning
confidence: 99%
“…The Mears criterion is satisfi ed in all cases: In the second stage in a study of the reaction modes, the wettability criterion of catalyst grains is determined. The authors of [9] recommend using the following criterial equation…”
Section: Resultsmentioning
confidence: 99%
“…For this purpose, the Peng-Robinson equation of state (Peng and Robinson, 1976) is implemented (Gauthier et al, 2007;Möller et al, 2009;Alvarez and Chen, 2014;Chávez et al, 2014). In this equation of state, the interaction coefficients between H 2 and hydrocarbons d H j that have been studied by some scholars (Tsonopoulos and Heidman, 1986;Chen et al, 2009;Chávez et al, 2014) are vital for the VLE calculation precision. In this work, the Tsonopoulos and Heidman (1986) correlation expressed as Eq.…”
Section: Modeling With Vlementioning
confidence: 99%
“…Most RTD studies on multi-phase reactors are performed under ambient conditions (Van Swaaij et al, 1969;Colombo et al, 1976;Iliuta et al, 1999;Kulkarni et al, 2005) and the volatility will be very low. Under typical reaction conditions, however, a significant amount of reactants can evaporate (Chen et al, 2009), and this will change the RTD function.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, a pressure drop over a reactor causes gas expansion, which enhances vaporization over the reactor length. Chen et al (2009) reported that at a typical temperature (350 1C) and pressure (50-100 atm) the weight percentage of hydrocarbon feed in the vapor phase could be in the range between 40% and 60%. Their feeds were light cycle oil (from a commercial fluid catalytic cracking unit), white cycle oil, and a mixture of both.…”
Section: Introductionmentioning
confidence: 99%